Therapeutic and prophylactic value of corrective gymnastics in children with impaired posture engaged in asymmetric sports - Tikhomirov A. Y., Minyaeva O. V., Tikhomirov R. A. (Interactive science, 2017)
the article provides the study that was conducted among young female athletes engaged in table tennis and having a violation of posture, with an assessment of metric and strength indicators. In the experimental group in parallel training a course of corrective gymnastics was conducted. The high efficiency of a combination of regular sports training and corrective gymnastics is established with a leveling of negative influence on the posture of asymmetrical sports.
Keywords: дети; спорт; нарушение осанки; настольный теннис; лечебная гимнастика; children; sports; table tennis; therapeutic gymnastics; violation of posture